Bluestem Horizon - Lee, Evelyn; Nang ChanYeema (Hong Kong Soundprints, 1998)
While growing up on the tallgrass prairie, Young Bison and his three companions experience both a tornado which separates them from the herd and a prairie fire brought on by lighting.
Keywords: Story Collection